Analisis Penempatan Kontainer dan Penggunaan Lashing Manual terhadap Tingkat Keamanan Muatan Kontainer di MV. Pulau Nunukan - Musthofa, Abi; Sa'adah, Nor; Widodo, B.L Hentri (Politeknik Bumi Akpelni Semarang, 2026)
Transporting container cargo by sea carries a high risk of cargo shifting and damage if containers are not positioned and lashed according to safety standards. Improper container positioning and suboptimal use of manual lashing can affect ship stability and cargo safety during voyages. This study aims to: 1). Determine the impact of container placement on the effectiveness and safety of container cargo, 2). Determine the importance of lashing as a preventive measure against damage and failure of container cargo safety functions, 3). Evaluate how the use of lashing and cargo placement conditions affect cargo safety levels. The method used is a quantitative approach with data collection through questionnaires distributed to 9 crew members of MV. Pulau Nunukan. Data analysis was performed using validity, reliability, normality, multicollinearity, heteroscedasticity tests, as well as multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the study indicate that cargo placement and the use of manual lashing each have a significant effect on cargo safety levels. Simultaneously, both variables also have a significant effect with a coefficient of determination value of 85.3%.